Wildlife Biodiversity in Bhawal National Park: Management Techniques and Drawbacks of Wildlife Management and Nature Conservation - Kabir, D.S.; Ahmed, A.Z. (Our Nature, 2006)
This paper emphasizes wildlife biodiversity and the management techniques and drawbacks particularly in Bhawal National Park. The park was declared a National Park in 1982; there was a great diversity of animal species at Bhawal National Park especially peafowl and jungle fowl dating back, to the British era as well as the Pakistani era. But unfortunately during and after 1971 there were neither reports nor any sighting of these attractive creatures. It is also remarkable; the remaining creatures such as civet, skunk, mongoose etc are endangered as well. The park management techniques and how they can be improved in order to preserve wildlife from the viewpoint of the Forest Department as the villagers couldn’t give any. Information through field observations, interviews and focus group discussions were collected. Conservation is the only alternative measure remaining for the rapidly dwindling small area of the Sal forest; The WMNCC will definitely have to come into effect if a consensus and status of the existing wildlife is to be published; The park management staff can also put up some colorful signboards depicting what species of wildlife that the tourist can find; Co-management of protected areas has great importance for conservation. Key words: Bhawal National Park, Management technique, Nature conservation, Wildlife biodiversity doi:10.3126/on.v3i1.340 Our Nature (2005) 3: 83-90